STUDENTS' PERSPECTIVES OF ONLINE LANGUAGE LEARNING DURING CORONA PANDEMIC: BENEFITS AND CHALLENGES - Jomana S. Zboun; Mohammed Farrah (Indonesian EFL Journal, 2021)
This study aimed to elicit students' perspectives towards benefits and challenges of fully online classes at Hebron University. The researchers examined both advantages and challenges of online classes from students' point of view. Also, they explored some suggestions for improving online classes which could play an important role in improving the online learning and teaching process. The researchers employed quantitative methods. They distributed a questionnaire to collect data. Eighty two students from two different English intensive courses were asked to fill a 5 point Likert scale questionnaire and answer four open-ended questions. The researchers used the survey planet app to facilitate the process of distributing and collecting data. The finding of this study showed that students faced some challenges with online learning; they preferred face to face classes. The disadvantages of online classes from their perspectives are more than the advantages. The weak internet connectivity, poor interaction, less motivation, less participation and less understanding are the most challenges of online learning. However, they find online classes easy to access, convenient and easy to be reviewed for exams.Keywords: Online learning; advantages; challenges